Two-body Abrasive Wear Behavior of Nylon 6 and Glass Fiber Reinforced (GFR) Nylon 6 Composite. (2016) - Kumar, Sudhir; Panneerselvam, K.
Abstract: Polymer composite materials are replacing traditional metal materials in many engineering applications due to their attractive properties such as excellent strength and stiffness to weight ratio, chemical resistance, corrosion resistance and low processing cost. In this experimental study, the mechanical and abrasive wear behavior of the Nylon 6 and GFR Nylon 6 composites was determined. Nylon 6 and GFR Nylon 6 composites specimen was fabricated for mechanical and wear test using injection molding machine. Wear test was carried out under dry condition against 320 grit size abrasive paper using pin-on-disc configuration. The effect of varying glass fiber contents (0, 10, 20 and 30 wt. %), applied loads (5, 10, 15 and 20 N), sliding distance 500 m were studied at 23 0 C temperature under humid atmospheric condition. The results showed that as the glass fiber content increases, specific wear rate decreases and it is lowest achieved at 30 wt. % of glass fiber. The analysis shows that the abrasive weight loss increases with increases of load. Microstructural analysis of worn surface was investigated by using scanning electron microscope and optical microscope.